Compatibility of Piper retrofractum and Annona squamosa extract mixture against Spodoptera frugiperda (Lepidoptera: Noctuidae) - Hamdan Maruli Siregar; Dadang Dadang; Dewi Sartiami; I Wayan Winasa; Siska Efendi; Gusti Indriati (Universitas Lampung, 2026)
Dependence on synthetic insecticides for controlling Spodoptera frugiperda has led to various adverse effects, including pest resistance, mortality of non-target organisms, and environmental pollution. These concerns necessitate the development of alternative control strategies, such as botanical insecticides that are both effective and environmentally friendly. Therefore, this study aimed to evaluate the toxicity and potential synergistic interactions of a hexane extract mixture of Piper retrofractum (Pr) and Annona squamosa (As) against second-instar larvae of S. frugiperda. Toxicity assays were conducted using the feed residue method in a completely randomized design with five extract mixture ratios of Pr:As (3:1, 2:1, 1:1, 1:2, and 1:3 w/w), each replicated five times. The results showed that the 2:1 (w/w) ratio was the most effective combination, yielding the lowest LC50 and LC95 values of 0.03% and 0.12%, respectively, at 96 hours after treatment. A higher proportion of Pr in the extract mixture tended to produce faster and more pronounced lethal effects on S. frugiperda larvae, and vice versa. The 2:1 (w/w) ratio also exhibited strong and stable synergistic interactions at all observation times at both LC50 and LC95 levels. This enhanced effectiveness is likely attributable to synergistic interactions among the active compounds present in each extract. These findings indicate that a mixture of P. retrofractum and A. squamosa extracts at a 2:1 (w/w) ratio has strong potential as an effective and efficient botanical insecticide to support the implementation of sustainable integrated pest management strategies.